Experimental Investigation on Modified Solar Still Using Nanoparticles and Water Sprinkler Attachment - Gupta, Bhupendra; Kumar, Anil; Baredar, Prashant V. (Frontiers in Materials, 2017)
The experimental investigation has been done in the month of April 2015 for climate condition of Jabalpur, Madhya Pradesh, India (latitude 23o18ˈN; Longitude 79o 95ˈE) during full day, 06.00 AM to 06:00 PM. The performance of the solar still with modification of water flow over the glass cover (sprinkler attachment) and nano particles (cuprous oxide) in basin water has been observed, recorded and compared with conventional still. It has been found that the collection of pure water in modified solar sill was 4000 ml/(m2-day) as compared to 2900 ml/(m2-day) in conventional solar still. The efficiency of 34% and 22% has been obtained for modified solar still and conventional still respectively. With design amendments, increase in overall effectiveness was found to be 54.54 %. The computed cost of pure water produced in modified still is expected to (INR) Rs.0.98/liter, in view of 12 yrs life of the solar still.